Directorate S. : The C.I.A. and America's Secret Wars in Afghanistan and Pakistan, 2001-2016 - Coll, Steve (UK Allen Lane, 2018)
Traces America's intelligence, military, and diplomatic efforts to defeat Al Qaeda and the Taliban in Afghanistan and Pakistan in the years since 9/11, and how the U.S. efforts in the Afghan War faltered because of a failure to understand the intentions of Pakistan's intelligence agency
Include Illustration, Notes, Bibliography and Index
Keywords: United States. -- Central Intelligence Agency -- Pakistan. -- Inter Services Intelligence -- Taliban